Application of electrochemical activated solution on broccoli seeds - Hai, Nguyen Thi Thanh; Anh Dung, Truong; Thi Quy, Nguyen (Vietnam Journal of Science and Technology, 2021)
Electrochemical activated solution possesses a wide variety of antimicrobial activities. Electrochemical activated solution (EAS) has been known as a super disinfectant solution with the promote ability in killing most of bacteria and fungi and safe for human use. Therefore, it has been studied and used in many different areas of life such as medication, food processing industry, etc., However, there are few reported the effect of EAS in agriculture. This study was conducted to determine the effects of using EAS to treat broccoli seeds on seed germination rate and growth of sprouts. The EAS was generated from KCl solution, the EAS was diluted with distilled water at 1.0, 0.9, 0.8, 0.7, 0.6, 0.5, 0.4, 0.3, 0.2 and 0.1 strengths of the source EAS. The results showed that treating seeds with EAS could reduce the quantity of microorganism on the surface of broccoli seeds, without affecting seed germination rate and sprout growth. The 0.3 strength EAS (pH 6,7; oxidants concentration of 8,6 ppm; ORP 560 mV) was the most suitable solution for microorganism killing on broccoli seeds.